Pendidikan Anti Korupsi Bagi Calon Tenaga Kerja Indonesia di PT. Global Lubna Jaya Sukoharjo - Agus Santoso, Aris Prio; Irawan AM, Ady (UNIB Press, 2024)
Indonesian workers abroad often face different work environments compared to Indonesia, including stricter ethical and moral standards. They represent the nation in their host countries. Anti-corruption education for prospective Indonesian workers can help build a positive image of professionalism and integrity, increasing other countries' trust in their quality and work ethics. The goal of this education is to develop a firm stance against workplace corruption both domestically and abroad. The community service partner is PT. Global Lubna Jaya Sukoharjo. The service method is online, using simulations and case studies. Results show significant understanding of anti-corruption culture among the participants, who commit to avoiding corrupt practices and fighting corruption together.